Capturing the Wealth From Tuna: case stude's from the Pacific - Barclay, Kate (ANU Press, 2008)
The Western and Central Pacific Ocean is home to the largest tuna fishery in the world - around half of the world's tuna supply - and is a vital economic resource for Pacific island countries. The potential of the Pacific tuna fishery to contribute to economic development in the Pacific island countries is enormous, but will require a cooperative regional strategy to maximise access fees from distant water fishing nations, as well as targeted domestic policy and legislation to encourage local fishing industries. Together with the importance of acting strategically with regard to such a variable resource, the lesson of fisheries management globally is that it is most effective when it takes into consideration social, cultural and political contexts. Based on an extensive study of six Pacific island states, Capturing Wealth from Tuna maps out the aspirations and limitations of six Pacific island countries and proposes strategies for capturing more wealth from this resource in a sustainable and socially equitable manner.